To Charge or Not to Charge: Examining Stakeholder Perceptions of Nonrevenue Sports Ticketing Policies - Peyton Stensland; Jordan Bass (Journal of Applied Sports Management, 2017)
All across college campuses, dozens of intercollegiate sports teams compete each year. It is assumed that attendance will vary across these sports for a number of factors. However, the impact of one organizationally controlled factor (choosing to ticket the event or not) has not been explored in the literature. In this study, the authors examined the ticketing practices of intercollegiate athletics departments. A qualitative interview approach was utilized to explore the importance and implications of ticketing practices of intercollegiate athletics departments. Terms such as reputation, legitimacy, and value were used to describe the reasoning behind whether or not to charge attendees at sporting events. Subscribe to JASM
Keywords: Ticketing policies; nonrevenue sports; intercollegiate athletics; qualitative; legitimacy; attendance; reputation; finance; sales